Pengaruh Content Marketing yang bertemakan lingkungan dan Green Attitude terhadap Minat Beli Skincare Ramah Lingkungan Avoskin - Zahra, Annisa; Adialita, Tania (Universitas Batanghari, 2024)
This study aims to analyze the influencet of content environmentally-themed content marketing and green attitude on the buying interest of environmentally friendly skincare products, Specifically Avoskin. The research method used is a quantitative approach conducted using Google Forms. Data collected from a number of respondents who were aware of Avoskin products and had been exposed to Avoskin’s environmentally-themed content marketing. The reseacrh variabels were measured using a likers scale ranging from 1-5. The sampling method used is convenience sampling, which fall under the category of nonprobability sampling. Data collection for this study was conducted cross-sectional, or as a one shot study. The involved validity testing, reliability testing, multiple linear regression analysis, and hypothesis testing. The results showed that environmental-themed content marketing had a positive and significant influence on the purchase intention of Avoskin’s eco-friendly skincare products. In contrast, green attitude, although exhibited a very favorable attitude towards environmentally-themed content marketing, partially did not have a significant influence on purchase intention. However, when both independent variables were analyzed simultaneously, it was found that eco-friendly content marketing and green attitude together have an influence on purchase intention.